Expression of osteopontin-5 splice variant in the mouse primary and metastatic breast cancer cells - Mohammad Kamalabadi-Farahani; Amir Atashi; Zahra Jabbarpour; Seyed Sajjad Aghayan (BMC Research Notes, 2022)
Abstract Objective Osteopontin (OPN) is a well-known glycoprotein involved in numerous pathobiological processes, including cancer. Despite having five splice variants for osteopontin in mice, the main focus of most studies has been on total OPN (tOPN). There are some studies on other splice variants, but the expression of osteopontin-5 (OPN5) has not been addressed in mouse cancer cells. Therefore, this study sought to evaluate OPN5 expression in mouse breast cancer cells. Results The expression of OPN5 in primary and metastatic breast cancer cells of mice was confirmed in our study. These findings provided important insights regarding the OPN alternative splicing in mice for the first time. It is concluded that, like other OPN-SVs, OPN5 probably plays an essential role in tumor progression, which requires further investigation in different tumor models.